DUKUNGAN LINGKUNGAN LITERASI KELUARGA MUSLIM TERHADAP PERKEMBANGAN KEMAMPUAN MEMBACA LATIN DAN ARAB (ALQUR’AN) SERTA PERKEMBANGAN AKADEMIK ANAK - Aguswan Khotibul Umam (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2016)
Reading and writing are the basic aspects that determine children’s academic development. In the aspect of Islamic knowledge development, Arabic and/or the Qur’an reading and writing skill become children’s basic academic development of Islamic knowledge. The effect of Family literacy will be an introduction in early reading and always will be influencing the children until they join the school. Children gain knowledge and experience of pre-reading as well as utterance: through social interaction with parents and family instead of formal learning. Appropriate Muslim family environment, reading atmosphere, and intensive Islamic studies will provide the great value of children’s Arabic (the Qur’an) reading and writing skill and of the true religious understanding and worship.